Third: A Screenplay on the Importance of Acceptance in an Attempt to Move on from Grief - Vincentius Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
Although everyone must have gone through a stage of grief in their life, often times people are not aware of how to properly deal with it and are having difficulties to move on. There is a misconception in the society that mourning is a negative emotion that one should get over with as soon as possible. Using the Tasks of Grief theory, however, I discovered that this misconception of the grieving process tends to lead someone into denial, as they are not urged to accept the emotions carried out by the grief. To illustrate how denial can hinder someone from finding closure to their grief, I created a fifteen-minute screenplay which tells the story of a man who seems to have moved on from his breakup with an ex-lover while, in fact, he is living in a denial by his attempt to mask his own emotions. After a series of event, the protagonist gradually comes to accept the true nature of his loss and finally moves on with his life. I hope that this creative work will influence the audience and society to remove the misconception of suppressing emotions and forgetting the deceased being a way out of their grief.